Implications of the Implementation of the Tax Administrative Sanctions Policy on Taxpayer Compliance - Wijaya, Haris Pandi (Universitas Pelita Harapan, 2023)
General provisions on taxation in Indonesia have regulated tax administration sanctions. The regulation and application of tax administration sanctions is expected to encourage taxpayer compliance. Through taxpayer compliance, tax revenue can reach the target on an ongoing basis. However, in reality, tax revenues in Indonesia tend to never reach the target. This is due to the still weak taxpayer compliance. Departing from this situation, this study examines the regulation of tax administration sanctions and their effectiveness in increasing taxpayer compliance. This research is a juridical-normative research. Data was collected through a study of documents originating from legal materials, both primary, secondary and tertiary. The research finding is that changes to the provisions on tax administration sanctions based on Law Number 7 of 2021 concerning Harmonization of Tax Regulations can encourage taxpayer compliance because these changes are marked by a reduction in sanctions that are not burdensome to taxpayers and are better able to reflect proportionality, convenience, and fairness compared to provisions previously. However, the application of tax administration sanctions in encouraging tax compliance still faces obstacles, namely that there is no adequate infrastructure in supervising and examining all taxpayers who commit tax non-compliance, the quantity and quality of tax officials in supervising and examining taxpayers, and the attitude of taxpayers who commit tax avoidance rather than fulfilling tax obligations.